2013
DOI: 10.1111/j.2047-2927.2013.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of udenafil in Turkish men with erectile dysfunction of psychogenic and organic aetiology: a randomized, double‐blind, placebo‐controlled study

Abstract: SUMMARYUdenafil is a potent phosphodiesterase type-5 inhibitor (PDE5) previously shown in studies conducted in populations of EasternAsian ethnicity, to significantly improve sexual function, in addition to a favourable safety profile. The purpose of this study was to evaluate the efficacy and safety of udenafil for the treatment of erectile dysfunction (ED), for the first time in a non-Eastern-Asian population. In this multicentre, randomized, double-blind, parallel, placebo-controlled study conducted in five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
(61 reference statements)
0
12
0
5
Order By: Relevance
“…Three of these studies 233,234,238 reported significant improvement of psychosocial outcomes (limited to IIEF satisfaction domains) vs placebo.…”
Section: Udenafilmentioning
confidence: 95%
“…Three of these studies 233,234,238 reported significant improvement of psychosocial outcomes (limited to IIEF satisfaction domains) vs placebo.…”
Section: Udenafilmentioning
confidence: 95%
“…A Phase II, double-blind, placebo-controlled, multi-center, parallel-group clinical trial showed that udenafil produced a highly significant improvement in erectile function, with an up to 91% vaginal penetration success rate 53. The clinical efficacy of udenafil in patients with ED of a variety of underlying etiologies, severities, and ages of the patients has been suggested in several randomized, placebo-controlled trials 2729,3133. Patient characteristics, outcome measures, and results of these trials are summarized in Tables 1 and 2.…”
Section: Efficacy Of Udenafil In Edmentioning
confidence: 99%
“…A recent multicenter, randomized, double-blind, placebo-controlled, parallel-group study assessed the efficacy and safety of 8-week 100 mg udenafil treatment in 118 Turkish men aged 19 to 70 years with ED of organic or psychogenic etiology 33. The primary efficacy variable was change from baseline in IIEF-EF scores.…”
Section: Efficacy Of Udenafil In Edmentioning
confidence: 99%
See 2 more Smart Citations